2008
DOI: 10.1017/s0305000908009227
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of Dutch connectives; how cumulative cognitive complexity explains the order of acquisition

Abstract: Before they are three years old, most children have started to build coherent discourse. This article focuses on one important linguistic device children have to learn: connectives. The main questions are: Do connectives emerge in a fixed order? And if so, how can this order be explained? In line with Bloom et al. (1980) we propose to explain similarities in the development in terms of cumulative cognitive complexity: complex relations are acquired later than simple ones. Following a cognitive approach to cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 22 publications
(35 reference statements)
3
74
0
1
Order By: Relevance
“…More importantly, each primitive has been associated with psycholinguistic evidence from experimental and corpus-based studies, which showed that these binary distinctions are indeed cognitively relevant and used by language users in processing or in acquisition. For instance, positive relations are acquired before negative ones, and additives before causals (Evers-Vermeul & Sanders, 2009).…”
Section: Cognitive Primitivesmentioning
confidence: 99%
“…More importantly, each primitive has been associated with psycholinguistic evidence from experimental and corpus-based studies, which showed that these binary distinctions are indeed cognitively relevant and used by language users in processing or in acquisition. For instance, positive relations are acquired before negative ones, and additives before causals (Evers-Vermeul & Sanders, 2009).…”
Section: Cognitive Primitivesmentioning
confidence: 99%
“…They want to exclude the possibility that a particular occurrence of a connective does not reflect the relevant knowledge of the child concerning the meaning of the connective. Evers-Vermeul and Sanders (2008) on the other hand use a qualitative criterion in their study on the acquisition of connectives. They take one occurrence of a connective as an indication that this particular connective is acquired.…”
Section: Resultsmentioning
confidence: 99%
“…In their study on the acquisition of the German focus particles auch 'also' and nur 'only', Berger & Höhle (2012) show that children (as young as three years old) are able to correctly interpret presupposition triggers like focus particles as long as the presupposed information is made sufficiently salient. For example, Evers-Vermeul & Sanders (2009) show that the cognitive complexity of a discourse relation is an important factor in the order of acquisition of the connectives that mark these relations. Bergsma 2006) had reported that children up to school age interpret sentences containing focus particles in the same way as sentences without them.…”
mentioning
confidence: 99%